Remarks on the hardy inequality - Hurri–Syrjänen R (Journal of Inequalities and Applications, 1997)
Let be an open subset of with finite Lebesgue -measure, let be the distance from to the boundary of , and let . We give a simple direct proof that if satisfies the plumpness condition of Martio and Väisälä [10], then the inequality of Hardy type, holds whenever . We also show that the plumpness condition may be replaced by ones. which enable domains with lower-dimensional portions of their boundaries to be handled.